Spatial and Temporal Variations in Crustal Structure in the Eurasian Basin - Lihong Zhao; Tao Zhang; Zilong Ling; Mujie Li; Pengyao Zhi; Renwei Ding; Chaoyang Li (Journal of Marine Science and Engineering, 2022)
To understand the tectonic–magmatic history, crustal structure and crustal accretion mode of the Eurasian Basin in the Arctic, we calculated the crustal thickness, residual bathymetry (RB) and non-isostatic topography of the Eurasian Basin by using the latest bathymetry, free-air gravity anomaly, crustal age and sediment thickness data. The tectonic–magmatic process of the Eurasian Basin can be divided into two stages. During magnetic isochrons 24-13 (C24-C13), the crustal structure of the basin was characterized by regional variations, while the crustal structure of the basin was characterized by local variations during magnetic isochrons 13-0 (C13-0). On the whole, the western part of the basin had a thicker crustal thickness and higher RB than the eastern part of the basin during C24-C13, which should result from the northward movement of Greenland. During magnetic isochrons 24-20 (C24-C20), the crustal structure of the eastern part of the basin had abnormally strong asymmetry. We speculate that there may be mantle upwelling beneath the Kara Sea Shelf in the south of the Eastern Eurasian Basin, which provides a large amount of melt for the crustal accretion of the southern part of the Eastern Eurasian Basin. The melt focusing supply could generate abnormally thick crust (>7 km) during magma enhancement period. The Western Eurasian Basin had stronger spatial variability and more frequency asymmetric polarity reversal than the Eastern Eurasian Basin during magnetic isochrons 6-0 (C6-0). We attribute this to the inflow of the North Atlantic mantle.